Twitchy pain of left face: a rare case of idiopathic trigeminal neuralgia after tooth extraction in a young child / Abdul Rauf Badrul Hisham ... [et al.] - Badrul Hisham, Abdul Rauf; Siddiqua, Niher Tabassum; Abdullah, Mohd Faizal; Wan Rossly, Wan Nur Syazwani; Samsudin, Norsamsu Arni (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Introduction: Idiopathic Trigeminal neuralgia in children is a rare case presentation that poses a challenge in dental practice. This case involved a sequence of multi-management by several departments including Paediatric Dentistry, Oral Maxillofacial Surgery (OMFS), Otorhinolaryngology (ORL) and Paediatric Neurology. Case description: A 10-year-old girl was referred initially to the Paediatric Dentistry Specialist Clinic, School of Dental Sciences, Universiti Sains Malaysia (USM), Malaysia with the complaint of left facial pain associated with muscle twitching, weakness and swelling for five days prior to this first visit. There was a history of tooth extraction of her lower left second primary molar on the day before the episode of left facial pain and twitching. Clinical examination showed left facial involuntary twitching with visual analogue scale (VAS) pain score of 8, some evidence of left facial weakness, numbness but no facial swelling. No significant finding on the intraoral examination, including good healing signs at the exodontia site. The investigations included orthopantomography, Cranial Nerves II-XII examination and tests, blood investigations, Blood Urea and Serum Electrolyte (BUSE), electromyography (EMG) and electroencephalogram (EEG). The final diagnosis was left Idiopathic Trigeminal Neuralgia that is associated with tooth extraction. After a period of a month, the symptoms and signs were gradually reduced and ceased by taking oral medications such as Baclofen, Neurobion and Gabapentin. Joint management from multi-departments with close follow ups help to provide the conservative and safe treatment for this patient.